Biomechanical control of beech pole verticality (Fagus sylvatica) before and after thinning: theoretical modelling and ground‐truth data using terrestrial LiDAR. Issue 2 (11th February 2019) - Noyer, Estelle; Fournier, Mériem; Constant, Thiéry; Collet, Catherine; Dlouhá, Jana
Abstract : Premise of the Study: Thinning is a frequent disturbance in managed forests, especially to increase radial growth. Due to buckling and bending risk associated with height and mass growth, tree verticality is strongly constrained in slender trees growing in dense forests and poor light conditions. Tree verticality is controlled by uprighting movements implemented from local curvatures induced by wood maturation stresses and/or eccentric radial growth. This study presents the first attempt to compare the real uprighting movements in mature trees using a theoretical model of posture control. Methods: Stem lean and curvature were measured by Terrestrial LiDAR Scanner (TLS) technology before and 6 years after thinning and compared to unthinned control poles. Measures for several tree and wood traits were pooled together to implement a widely used biomechanical model of tree posture control. Changes in observed stem lean were then compared with the model predictions, and discrepancies were reviewed. Key Results: Even under a highly constrained environment, most control poles were able to counterbalance gravitational curvature and avoid sagging. Thinning stimulated uprighting movements. The theoretical uprighting curvature rate increased just after thinning, then slowed after 2 years, likely due to the stem diameter increase. The biomechanical model overestimated the magnitude of uprighting. Conclusions: Most suppressed beech poles maintain a constant lean angle, and uprighting movements occur after thinning, indicating that stem lean is plastic in response to light conditions. Acclimation of posture control to other changes in growth condition should be investigated, and lean angles should be measured in forest inventories as an indicator of future wood quality.